Schooling and Governance: Pedagogical Knowledge and Bureaucratic Expertise in the Genesis of the Argentine Educational System - Southwell, Myriam Monica (2013)
The constitution of the Federal Government meant to modernise local societies, produce institutional complexes and reach political stabilisation. The deployment of modern schooling articulated utopia and bureaucracy using the image of knowledge as an instrument of social intervention, vindicating and legitimising the concept of rational control. These coordinates established the formal and material bases to constitute the pedagogical knowledge on the one hand, and a field of bureaucratic knowledge on the other hand. These fields involved different ways of articulating the regulation devices of the educational system. If the normalist pedagogical knowledge involved a set of instructions on schooling, the bureaucratic knowledge of inspectors resulted in the schooling process regulations.